Investment Regulations in the Development of Tourism Services for Persons With Disabilities - Ida Bagus Ariawan (Journal Equity of Law and Governance, 2025)
Disabled tourists represent a significant market segment in the tourism industry due to their large numbers and growth potential. They face physical, mental, intellectual, or sensory limitations that hinder full participation in tourism activities. In this context, they are entitled to specific facilities, including accessible destinations, transportation, and accommodations. Law Number 10 of 2009 does not specifically regulate tourism as a service trade, but rather certain aspects such as transportation, accommodation, food services, and others. Although tourism services for persons with disabilities are available in Indonesia, current systems have yet to optimize this market’s potential. Existing policies remain general and do not adequately address the specific needs of disabled tourists. Based on this, the study explores: (1) how investment in tourism services for disabled persons is currently regulated, and (2) how regulatory frameworks can be constructed to align with the characteristics of disabled tourists. This normative legal research applies statutory and conceptual approaches.